English vocabulary in use pre-intermediate and intermediate - Redman, Stuart (Cambridge University Press, 2004)
A new edition of the best-selling vocabulary practice title. Whether you're studying on your own or in class, English Vocabulary in Use Pre-intermediate and Intermediate covers all the words and phrases you need at this level to understand and be understood in English. This new edition is fully updated to make the book even more relevant and accessible. The updated CD-ROM provides hundreds of extra practice activities, an in-built dictionary and interactive games.
Keywords: lingvistika, lékařská terminologie; ANGLIČTINA